Coke oven silica brick and preparation method thereof

By using CaO-Al2O3-type mineralizer and pre-firing technology in silicon bricks for coke ovens, the problem of gas release at high temperatures in traditional silicon bricks is solved, the density and thermal conductivity of silicon bricks are improved, and it is suitable for industrial production.

CN119683981APending Publication Date: 2025-03-25INSPECTION & CERTIFICATION CO LTD MCC +1

Patent Information

Application Number
CN202411646951.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The traditional coke oven uses silicon bricks to decompose mineralizers to produce gas at high temperatures, resulting in poor density and thermal conductivity of bricks. In the prior art, Al2O3 is regarded as an impurity in silicon bricks, making it difficult to effectively improve the refractory and thermal conductivity of silicon bricks.

Method used

CaO-Al2O3-based mineralizer is used to add calcium nitrate tetrahydrate and high-silicon aluminum alloy powder and combined with pre-firing technology to control the reaction path of high-silicon aluminum alloy in the brick at high temperature, forming gas phase SiO(g) and Al2O(g) to improve the density and thermal conductivity of the brick.

Benefits of technology

It has achieved the improvement of high density, strength and thermal conductivity of silicon bricks, and the firing process is easy to control, making it suitable for the industrial production of large silicon bricks.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, in particular to a coke oven silica brick and a preparation method thereof.The preparation method comprises the following steps that S1, silica fine powder, calcium nitrate tetrahydrate and high-silicon aluminum alloy powder are mixed to prepare pug 1; s2, pre-sintering the pug 1 at the temperature of 500 to 950 DEG C; s3, uniformly stirring silica aggregate, a binding agent and a material obtained after presintering in the step S2 to prepare pug 2; and S4, pressing the pug 2 into a green brick, and drying and sintering the green brick to obtain the coke oven silica brick. The CaO-Al2O3 mineralizer is used for producing the coke oven silica brick, and the reaction path of the high-silicon aluminum alloy in the brick at high temperature is controlled by a pre-sintering means, so that the heat-conducting property of the silica brick product for the coke oven is improved. The preparation method is simple, the raw materials are rich, the cost performance is excellent, the sintering process is easy to control, the preparation method is suitable for industrial production of large silica bricks, and the finished brick has excellent heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a coke oven silica brick and a preparation method thereof. Background Art

[0002] High thermal conductivity is the main direction of energy-saving development of silica bricks for coke ovens. Traditionally, silica bricks are produced with "lime milk + iron scale" as mineralizers, but there have always been many problems such as the difficulty in uniformly dispersing the mineralizer and the gas generated during the high-temperature decomposition of lime milk, which is easy to damage the brick structure. In particular, the gas generated by the high-temperature decomposition of lime milk is very detrimental to the density of the brick, and thus affects the thermal conductivity of the product.

[0003] Patent ZL 2022 1 1303558.8 "A silica brick with calcium nitrate tetrahydrate added and its preparation method" discloses the production of silica bricks using calcium nitrate tetrahydrate as a mineralizer, and the introduction of uniformly dispersed high-activity CaO into the bricks through the decomposition of calcium nitrate tetrahydrate. However, the addition of calcium nitrate tetrahydrate still has the problem of gas release generated by high-temperature decomposition, which is not conducive to the density and thermal conductivity of the brick body.

[0004] The above are the applicant's research findings, not all of which are prior art, and therefore cannot all be regarded as prior art. Summary of the invention

[0005] There is currently no 2 O 3 The precedent of using CaO as mineralizer to produce silica bricks, Al 2 O 3 It has always been considered as an impurity phase in silica bricks, and its content is generally between 0.3% and 1.3%. This is because there are both CaO and Al in silica bricks. 2 O 3 When Al 2 O 3 As the Al / CaO ratio increases, the amount of liquid increases dramatically, which is particularly significant at 1500°C, especially above 1600°C. However, if the CaO content in silica bricks is increased to more than 2% (the CaO content of traditional coke oven silica bricks is generally less than 2%), a small amount of Al 2 O 3 It can also improve the refractoriness of silica bricks. The working temperature of coke ovens is generally 1000-1300℃, which is far from 1500℃. Therefore, CaO-Al with high CaO ratio is 2 O 3 It is technically feasible to use calcium mineralizer in silica bricks for coke ovens. However, if lime milk is used as calcium mineralizer, its disadvantage of being difficult to disperse evenly will become more obvious as the amount added increases. Using calcium nitrate tetrahydrate as calcium mineralizer can achieve uniformity, but the problem of gas release generated by high-temperature decomposition still needs to be solved.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing coke oven silica bricks, comprising the following steps:

[0008] S1, mixing silica fine powder, calcium nitrate tetrahydrate and high silicon aluminum alloy powder to form mud 1;

[0009] S2, pre-burning the clay material 1 at 500-950°C;

[0010] S3, mixing silica aggregate, binder, and the material obtained after pre-burning in S2 together to make mud 2;

[0011] S4, pressing the mud 2 into a brick, and obtaining a coke oven silicon brick through drying and sintering steps.

[0012] Among them, the mass ratio of calcium nitrate tetrahydrate and high silicon aluminum alloy powder is controlled to be 10-60:1, which is conducive to constructing high CaO and low Al in the material. 2 O 3 material ratio.

[0013] Preferably, the mass ratio of calcium nitrate tetrahydrate to high silicon aluminum alloy powder is 10-40:1, preferably 10-20:1.

[0014] Preferably, the silicon mass content in the high-silicon aluminum alloy powder is above 20%, which is conducive to the formation of gas-phase SiO (g) at high temperature to increase the density of the silicon dioxide skeleton in the material.

[0015] Preferably, based on the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder, and silica aggregate, the mass percentage of calcium nitrate tetrahydrate is 10% to 30%, the mass percentage of high silicon aluminum alloy powder is 0.1% to 3%, and the mass percentage of silica fine powder is 15% to 45%. The use of silica fine powder, calcium nitrate tetrahydrate, and high silicon aluminum alloy powder in an appropriate mass ratio is more conducive to the transformation of quartz to tridymite during the firing process of silica bricks.

[0016] Preferably, the silica aggregate comprises a first silica aggregate and a second silica aggregate, wherein the particle size of the first silica aggregate is ≤ 2.5 mm and > 0.5 mm, and the particle size of the second silica aggregate is ≤ 0.5 mm. The use of the first silica aggregate and the second silica aggregate of two different particle sizes is more conducive to the formation of a dense stack of the particles in the material.

[0017] Preferably, based on the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder, the first silica aggregate and the second silica aggregate, the mass percentage of the first silica aggregate is 10% to 40%, and the mass percentage of the second silica aggregate is 30% to 70%, which is more conducive to improving the mechanical strength of the material.

[0018] Preferably, the mass dosage of the binder is 0.5% to 5% of the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder and silica aggregate.

[0019] Preferably, the particle size of the silica fine powder is ≤200 mesh, and the particle size of the high-silicon aluminum alloy powder is ≤80 mesh. The use of high-silicon aluminum alloy powder and silica fine powder with suitable low particle sizes is more conducive to the formation of a passivation layer on the surface of the powder and the reaction to form gas-phase metal oxides during high-temperature sintering.

[0020] Preferably, the silica fine powder and silica aggregate are crystalline silica, which is beneficial to reduce the Al introduced into the raw materials. 2 O 3 , which is more conducive to high CaO and low Al in materials 2 O 3 The formation of material ratio.

[0021] The high silicon aluminum alloy powder may be, for example, a mixture of one or more silicon aluminum alloys having Al-20Si and higher silicon contents.

[0022] Preferably, the pre-burning time in S2 is 1-6 h, preferably 2-6 h.

[0023] Preferably, in S4, the drying process comprises: drying the bricks at a temperature less than 200° C. for 24 to 48 hours until the residual moisture is less than 1.0 wt %.

[0024] Preferably, the sintering process includes: heating to a maximum of 1450-1510°C and maintaining the temperature for 24-48 hours for sintering, which is more conducive to the sintering reaction in the material.

[0025] In a second aspect, the present invention provides a coke oven silica brick, which is prepared by the method for preparing the coke oven silica brick described in the first aspect.

[0026] In a third aspect, the present invention provides a coke oven silicon brick, wherein the raw materials include silica fine powder, silica aggregate, calcium nitrate tetrahydrate and a binder, and the raw materials further include high-silicon aluminum alloy powder, wherein the silicon mass content in the high-silicon aluminum alloy powder is more than 20%, and the mass ratio of calcium nitrate tetrahydrate to the high-silicon aluminum alloy powder is 10-60:1; based on the total amount of silica fine powder, calcium nitrate tetrahydrate, high-silicon aluminum alloy powder and silica aggregate, the mass percentage of calcium nitrate tetrahydrate is 10%~30%, the mass percentage of high-silicon aluminum alloy powder is 0.1%~3%, and the mass percentage of silica fine powder is 15%~45%; the silica fine powder and silica aggregate are crystalline silica.

[0027] Preferably, the particle size of the silica fine powder is ≤200 mesh, and the particle size of the high-silicon aluminum alloy powder is ≤80 mesh.

[0028] Preferably, the mass dosage of the binder is 0.5% to 5% of the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder and silica aggregate.

[0029] Beneficial effects:

[0030] In the preparation method of the present invention, CaO-Al 2 O 3 The mineralizer is used to produce coke oven silica bricks, that is, CaO and Al are introduced into the material by adding calcium nitrate tetrahydrate and high silicon aluminum alloy. 2 O 3 As a mineralizer, (preferably using high purity crystalline silica to reduce the Al introduced into the raw materials 2 O 3 ), further control the reaction path of high silicon aluminum alloy in the brick at high temperature by pre-sintering, so that it can provide Al 2 O 3 The thermal conductivity of silica bricks for coke ovens can be improved by diffusion and deposition of gas-phase SiO(g) as mineralizers. The role of pre-burning can be summarized as at least two aspects: on the one hand, it promotes the decomposition of calcium nitrate tetrahydrate to form uniformly dispersed high-activity CaO, and at the same time prevents the decomposition of calcium nitrate tetrahydrate during the firing process of silica bricks from damaging the brick structure; on the other hand, pre-burning can oxidize the surface of high-silicon aluminum alloy powder to form an oxide coating layer. The melting point of high-silicon aluminum alloy is generally lower than 1000°C (the higher the aluminum content, the lower the melting point). The oxide layer coated on the surface of the alloy powder can wrap the alloy when the temperature exceeds the melting point of the alloy during the firing process of the silica brick to prevent it from reacting. When the firing temperatures reach 1360°C and 1430°C respectively, the uniformly dispersed high-activity CaO in the brick and the Al in the oxide coating on the surface of the alloy will react with each other. 2 O 3 and SiO 2 The reaction forms a liquid phase, which in turn destroys the oxide coating. Since the ambient temperature when the coating is destroyed is much higher than the melting point of the alloy, the molten alloy reacts rapidly after contacting the air to form a gas phase metal oxide Al 2 O(g) and SiO(g). Finally, through Al 2 The diffusion and oxidation deposition of O(g) and SiO(g) in the brick fill the tiny pores in the brick, improving the continuity of the brick skeleton structure and thus improving the thermal conductivity of the brick.

[0031] The present invention uses CaO-Al 2 O 3 The production of coke oven silica bricks by mineralizers, that is, by adding calcium nitrate tetrahydrate and high silicon aluminum alloy, at least the following beneficial effects are produced:

[0032] (1) The pre-burning process of the powder forms an oxide coating on the alloy surface, and also causes the mineralizer calcium nitrate tetrahydrate to decompose in advance, avoiding the decomposition of gas during the brick burning process that damages the brick structure and improves the density of the fired brick;

[0033] (2) Calcium nitrate tetrahydrate is converted into liquid phase due to frictional heat during the pre-mixing process. Liquid phase mixing realizes the uniform distribution of CaO in the powder, ensuring that the oxide coating on the alloy surface can be destroyed by CaO during the firing process of silicon bricks;

[0034] (3) The oxide coating layer constructed on the alloy surface by pre-sintering and the destruction of the oxide coating layer by CaO at high temperature make the high silicon aluminum alloy transform into gas phase metal oxide SiO(g) at high temperature. SiO(g) can fill the tiny pores in the brick through diffusion and deposition, thus improving the continuity of the brick skeleton structure and thus improving the heat transfer efficiency.

[0035] (4) The silica bricks of the present invention have a dense structure, high strength, high load softening temperature, and excellent thermal conductivity;

[0036] (5) The preparation method of the present invention is simple, the raw materials are abundant and cost-effective, the firing process is easy to control, and it is suitable for the industrial production of large-scale silica bricks. DETAILED DESCRIPTION

[0037] The present invention uses CaO-Al 2 O 3 The invention is a mineralizer for producing silica bricks for coke ovens. The reaction path of high silicon aluminum alloy in the bricks at high temperature is controlled by pre-burning means, so as to improve the thermal conductivity of silica bricks for coke ovens. The preparation method of the invention is simple, the raw materials are abundant and cost-effective, the firing process is easy to control, and it is suitable for the industrial production of large-scale silica bricks. The finished bricks have excellent thermal conductivity.

[0038] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail in conjunction with specific embodiments. Unless otherwise specified, the high silicon aluminum alloy is Al-30Si, that is, the silicon mass content is 30%, and the balance is aluminum; the particle size of the first silica aggregate is ≤ 2.5 mm and > 0.5 mm, and the particle size of the second silica aggregate is ≤ 0.5 mm.

[0039] Example 1

[0040] First, 15 wt% of silica fine powder, 1.5% of high silicon aluminum alloy, and 20 wt% of calcium nitrate tetrahydrate are mixed and pre-fired at 900℃ for 2h. Then, the pre-fired material is mixed with 25 wt% of the first silica aggregate, 38.5 wt% of the second silica aggregate, and 3 wt% of the total amount of the above mixture as a binder to form a mud material and press it into shape; after the drying process: the brick is dried at a temperature of less than 200℃ for 30h until the residual moisture is less than 1.0 wt%, and after drying, it is placed in a tunnel kiln and fired at 1470℃ for 40h to obtain a silica brick.

[0041] The obtained silica brick was tested and found to have an apparent porosity of 18.0% and a bulk density of 1.91 g / cm 3 The room temperature compressive strength is 62.7 MPa, the load softening temperature is 1669℃, and the thermal conductivity is 2.65 W / (m·k).

[0042] Example 2

[0043] First, 15 wt% of silica fine powder, 0.5% of high silicon aluminum alloy, and 15 wt% of calcium nitrate tetrahydrate are mixed and pre-fired at 800℃ for 3h. Then, the pre-fired material is mixed with 25 wt% of the first silica aggregate, 44.5 wt% of the second silica aggregate, and 3 wt% of the binder of the above mixture to form a mud material and press it into shape; after the drying process: the brick is dried at a temperature of less than 200℃ for 30 hours until the residual moisture is less than 1.0 wt%, and after drying, it is placed in a tunnel kiln and fired at 1450℃ for 40 hours to obtain a silica brick.

[0044] The obtained silica brick was tested and found to have an apparent porosity of 18.4% and a bulk density of 1.88 g / cm 3 The room temperature compressive strength is 58.6 MPa, the load softening temperature is 1672℃, and the thermal conductivity is 2.51 W / (m·k).

[0045] Example 3

[0046] First, 15 wt% of silica fine powder, 2.5% of high silicon aluminum alloy, and 25 wt% of calcium nitrate tetrahydrate are mixed and pre-fired at 950℃ for 3h. Then, the pre-fired material is mixed with 25 wt% of the first silica aggregate, 32.5 wt% of the second silica aggregate, and 4 wt% of the binder of the above mixture to form a mud material and press it into shape; after the drying process: the brick is dried at a temperature of less than 200℃ for 30 hours until the residual moisture is less than 1.0 wt%, and after drying, it is placed in a tunnel kiln and fired at 1480℃ for 30 hours to obtain a silica brick.

[0047] The obtained silica brick was tested and found to have an apparent porosity of 17.8% and a bulk density of 1.92 g / cm 3The room temperature compressive strength is 69.8 MPa, the load softening temperature is 1659℃, and the thermal conductivity is 2.79 W / (m·k).

[0048] Example 4

[0049] The same method is carried out as in Example 1, except that the pre-burning time is different, specifically 1 hour.

[0050] The obtained silica brick was tested and found to have an apparent porosity of 18.2% and a bulk density of 1.89 g / cm 3 The room temperature compressive strength is 59.8 MPa, the load softening temperature is 1662℃, and the thermal conductivity is 2.53 W / (m·k).

[0051] Example 5

[0052] The method is carried out in accordance with Example 1, except that the silicon content in the high silicon aluminum alloy powder is different, so that the mass content ratio of silicon to aluminum is 1:4.

[0053] The obtained silica brick was tested and found to have an apparent porosity of 18.1% and a bulk density of 1.90 g / cm 3 The room temperature compressive strength is 61.5 MPa, the load softening temperature is 1663℃, and the thermal conductivity is 2.60 W / (m·k).

[0054] Comparative Example 1

[0055] The process is carried out in accordance with Example 1, except that no high silicon aluminum alloy powder is added.

[0056] The obtained silica brick was tested and found to have an apparent porosity of 18.3% and a bulk density of 1.88 g / cm 3 The room temperature compressive strength is 58.1 MPa, the load softening temperature is 1671℃, and the thermal conductivity is 2.21 W / (m·k).

[0057] Comparative Example 2

[0058] The method is carried out in accordance with Example 1, except that the amount of high silicon aluminum alloy powder added is different, and the amount of high silicon aluminum alloy powder is controlled so that the mass ratio of calcium nitrate tetrahydrate to high silicon aluminum alloy powder is 5:1.

[0059] The obtained silica brick was tested and found to have an apparent porosity of 17.9% and a bulk density of 1.92 g / cm 3 The room temperature compressive strength is 63.5 MPa, the load softening temperature is 1605℃, and the thermal conductivity is 2.66 W / (m·k).

[0060] Comparative Example 3

[0061] The process is carried out in accordance with Example 1, except that no pre-firing is performed, but all raw materials are mixed and then stirred and mixed directly, and then pressed into bricks, dried, and sintered.

[0062] The obtained silica brick was tested and found to have an apparent porosity of 20.5% and a bulk density of 1.82 g / cm 3 The room temperature compressive strength is 49.1 MPa, the load softening temperature is 1640℃, and the thermal conductivity is 2.05 W / (m·k).

[0063] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing coke oven silica bricks, characterized in that: The steps include: S1, mixing silica fine powder, calcium nitrate tetrahydrate, and high silicon aluminum alloy powder to form a slurry 1; wherein the mass ratio of calcium nitrate tetrahydrate to high silicon aluminum alloy powder is controlled to be 10-60:1; and the silicon mass content in the high silicon aluminum alloy powder is above 20%; S2, pre-burning the clay material 1 at 500-950°C; S3, mixing silica aggregate, binder, and the material obtained after pre-burning in S2 together to make mud 2; S4, pressing the mud 2 into a brick, and obtaining a coke oven silicon brick through drying and sintering steps.

2. The preparation method according to claim 1, characterized in that: Based on the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder and silica aggregate, the mass percentage of calcium nitrate tetrahydrate is 10%~30%, the mass percentage of high silicon aluminum alloy powder is 0.1%~3%, and the mass percentage of silica fine powder is 15%~45%.

3. The preparation method according to claim 1, characterized in that: The silica aggregate comprises a first silica aggregate and a second silica aggregate, wherein the particle size of the first silica aggregate is ≤ 2.5 mm and > 0.5 mm, and the particle size of the second silica aggregate is ≤ 0.5 mm; based on the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder, the first silica aggregate and the second silica aggregate, the mass percentage of the first silica aggregate is 10% to 40%, and the mass percentage of the second silica aggregate is 30% to 70%; The mass dosage of the binder is 0.5%~5% of the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder and silica aggregate.

4. The preparation method according to any one of claims 1 to 3, characterized in that The particle size of the silica fine powder is ≤200 meshes, and the particle size of the high-silicon aluminum alloy powder is ≤80 meshes; the silica fine powder and silica aggregate are crystalline silica.

5. The preparation method according to claim 1, characterized in that: The mass ratio of calcium nitrate tetrahydrate to high silicon aluminum alloy powder is 10-40:

1.

6. The preparation method according to claim 1, characterized in that: The pre-burning time in S2 is 1-6 h.

7. The preparation method according to claim 1, characterized in that: In S4, the drying process includes: drying the bricks at a temperature less than 200°C for 24 to 48 hours until the residual moisture is less than 1.0 wt%; The sintering process includes: heating to a maximum temperature of 1450-1510° C. and maintaining the temperature for 24-48 hours for sintering.

8. A coke oven silica brick, characterized in that: The silica brick is prepared by the method for preparing a coke oven silica brick as described in any one of claims 1 to 7.

9. A coke oven silica brick, the raw materials of which include silica fine powder, silica aggregate, calcium nitrate tetrahydrate and a binder, characterized in that: The raw materials also include high-silicon aluminum alloy powder, the silicon mass content in the high-silicon aluminum alloy powder is more than 20%, and the mass ratio of calcium nitrate tetrahydrate to high-silicon aluminum alloy powder is 10-60:1; based on the total amount of silica fine powder, calcium nitrate tetrahydrate, high-silicon aluminum alloy powder and silica aggregate, the mass percentage of calcium nitrate tetrahydrate is 10%~30%, the mass percentage of high-silicon aluminum alloy powder is 0.1%~3%, and the mass percentage of silica fine powder is 15%~45%; the silica fine powder and silica aggregate are crystalline silica.

10. The coke oven silica brick according to claim 9, characterized in that: The particle size of the silica fine powder is ≤200 mesh, and the particle size of the high silicon aluminum alloy powder is ≤80 mesh; The mass dosage of the binder is 0.5%~5% of the total amount of silica fine powder, calcium nitrate tetrahydrate, high silicon aluminum alloy powder and silica aggregate.

Citation Information

Patent Citations

  • A silica brick with added calcium nitrate tetrahydrate and its preparation method

    CN115536409B

Cited By

  • Silica brick for coke oven and preparation method therefor

    WO2026103855A1